PAPR Reduction for Visible Light Communication Systems Without Side Information - Wei-Wen Hu; Da-Huei Lee (IEEE Photonics Journal, 2017)
It is well known that visible light communication (VLC) systems with the direct current-biased optical orthogonal frequency division multiplexing (DCO-OFDM) scheme suffers from high peak-to-average power ratio (PAPR), which leads to serve distortion and degradation of the output of light emitting diodes. Selected mapping (SLM) technique is an attractive PAPR reduction technique for radio frequency OFDM systems. However, conventional SLM (CSLM) techniques cannot be adopted directly in DCO-OFDM VLC systems because DCO-OFDM VLC signals are restricted to have positive real values. Moreover, CSLM requires transmission of side information (SI) to identify which candidate signal is selected. To avoid the transmission of SI, a novel phase sequence is proposed for the SLM scheme with blind SI detection in DCO-OFDM VLC systems. The proposed phase sequences consist of the magnitude extension and phase rotation factors, where the former factors enable the blind detection of SI, and the latter factors aim to decrease the PAPR. Particularly, the magnitude extension factors are designed to have the symmetry and periodicity. Compared with basic DCO-OFDM with no PAPR reduction scheme, the proposed scheme achieved significant PAPR reductions of 2.1 dB, 3.4 dB, 4 dB, and 4.2 dB for a complementary cumulative distribution function of $10^{-3}$ and $V=4$ , $V=8$ , $V=16$ , and $V=31$ , respectively. Simulation results show that the proposed schemes achieve comparable PAPR reduction performance with the CSLM scheme without the need for SI. Moreover, the proposed SI detection scheme achieves almost the identical bit error rate performance as the CSLM scheme with perfect SI detection with a slight increase in transmitted average power and lower computational complexity.